Comparison of tiletamine-zolazepam and tiletamine-zolazepam-ketamine-xylazine administered intravenously in dogs - Chen, Hui Cheng; Yeoh, H. Y.; Yeoh, E. C. (Veterinary Association Malaysia, 2005)
The anaesthetic effects of intravenous administration oftiletamine (2.5 mg/kg) - zolazepam (2.5 mg/kg) mixture (TZ), and tiletamine (0.5 mglkg) - zolazepam (0.5 mg/kg) - ketamine (1.6 mg/kg) - xylazine (0.4 mg/kg) mixture (TKX) were evaluated in ten dogs. Atropine sulphate at a dose rate ofO.05 mg/kg was administered concurrently with the anaesthetic mixtures. Both mixtures produced rapid, smooth induction, and allowed intubation. The TKX mixture produced longer skin clamp analgesia and immobilisation, better jaw relaxation, with shorter and smoother recovery compared to TZ injection. The TKX mixture induced significant but transient pallor of mucous membranes « 2 min). The TZ mixture resulted in increased heart rate and a higher respiratory rate compared to TKX mixture. Haemoglobin saturation was < 90% in some dogs following either mixture. The TKX mixture can be considered as an alternative injectable mixture to TZ for short and minimally invasive procedures in patients that have no cardiopulmonary dysfunction.